Health outcomes of online consumer health information: A systematic mixed studies review with framework synthesis. (30th January 2019) - Pluye, Pierre; El Sherif, Reem; Granikov, Vera; Hong, Quan Nha; Vedel, Isabelle; Galvao, Maria Cristiane Barbosa; Frati, Francesca E.Y.; Desroches, Sophie; Repchinsky, Carol; Rihoux, Benoît; Légaré, France; Burnand, Bernard; et al.
Abstract : The Internet has become the first source of consumer health information. Most theoretical and empirical studies are centered on information needs and seeking, rather than on information outcomes. This review's purpose is to explore and explain health outcomes of Online Consumer Health Information (OCHI) in primary care. A participatory systematic mixed studies review with a framework synthesis was undertaken. Starting from an initial conceptual framework, our specific objectives were to (a) identify types of OCHI outcomes in primary care, (b) identify factors associated with these outcomes, and (c) integrate these factors and outcomes into a comprehensive revised framework combining an information theory and a psychosocial theory of behavior. The results of 65 included studies were synthesized using a qualitative thematic data analysis. The themes derived from the literature underwent a harmonization process that produced a comprehensive typology of OCHI outcomes. The revised conceptual framework specifies four individual and one organizational level of OCHI outcomes, while including factors such as consumers' information needs and four interdependent contextual factors. It contributes to theoretical knowledge about OCHI health outcomes, and informs future research, information assessment methods, and tools to help consumers find and use health information.